Final stages of the Brasiliano Orogenesis in SE Brazil: U-Pb and 40Ar/39Ar evidence for overprinting of the Brasília Belt by the Ribeira Belt Tectonics - Hackspacher, P. C. [UNESP]; Fetter, A. H. [UNESP]; Teixeira, W.; Dantas, E. L.; Ebert, H. D. [UNESP]; Trouw, R. A. J.; Vasconcelos, P. (My University, 2004)
Around the southern margins of the São Francisco Craton, there is a zone of tectonic interference between the Brasília belt to the west and the younger Ribeira belt to the east. U-Pb monazite and 40Ar/39Ar cooling age determinations carried out in the area reveal the cooling histories of these belts and the timing of tectonic overprint, unraveling the final stages of Brasiliano Orogeny in SE Brazil. The U-Pb monazite data from migmatized paragneisses and late-stage pegmatites in the Socorro-Guaxupé Nappe System of the southern Brasília belt show that migmatization peaked between ca. 613±1 and 607±3 Ma. 40Ar/39Ar biotite and muscovite ages of paragneisses and schists in this area indicate that the northern high-grade core of the Nappe System (Guaxupé Domain) was uplifted and cooled through the 350°C isotherm between 599±1 and 587±1 Ma. In contrast, samples from the southern high-grade core of the Nappe System, the Socorro Domain, south of the Jacutinga shear zone, yields a broader and younger spectrum of 40Ar/39Ar biotite ages between 571±1 and 562±1 Ma, attributed to a later uplift and cooling of the crust. The cooling ages can be assigned to local resetting of the 40Ar/39Ar system during transpressive tectonic overprint due to reactivation as a result of collision of the Ribeira belt. A younger group of 40Ar/39Ar mica ages (537±1 to 521±1Ma) in schists of the Socorro Domain, are associated with transpressional structures of the Ribeira belt. Rock samples from the Jacutinga and Três Corações shear zones, yield 40Ar/39Ar biotite-muscovite ages around 520 Ma. These are typical cooling ages of the Ribeira belt, and are interpreted to mark the western limit of the Ribeira belt transpressional regime within the Brasília belt. The youngest biotite-muscovite cooling ages in schists of the Socorro Domain, between 510±2 and 491±1 Ma, mark the final cooling and exhumation of that part of the Brasília belt.
Keywords: Ar-Ar; Brasiliano orogen; Ribeira Belt; Tectonics; U-Pb